2016
DOI: 10.1007/s11356-016-6805-z
|View full text |Cite
|
Sign up to set email alerts
|

Breakage and regrowth of flocs formed by sweep coagulation using additional coagulant of poly aluminium chloride and non-ionic polyacrylamide

Abstract: The breakage and regrowth of flocs formed by sweep flocculation were investigated on different flocculation mechanisms using additional dosage coagulant of poly aluminium chloride (PACl) and non-ionic polyacrylamide (PAM) to explore the reversibility after floc breakage. The optimal dosage of PACl was 0.15 mM (as alum), and zeta potential exceeding 1 mV meant that sweep flocculation was dominant in the pre-flocculated process. Re-coagulation efficiency increased with additional coagulants dosing, and sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The zeta potentials were also the same before and after the breakage, which indicated that the vigorous stirring had no impact on the zeta potential. This similar phenomenon has been found in previous research [31]. …”
Section: Resultssupporting
confidence: 92%
“…The zeta potentials were also the same before and after the breakage, which indicated that the vigorous stirring had no impact on the zeta potential. This similar phenomenon has been found in previous research [31]. …”
Section: Resultssupporting
confidence: 92%
“…A hybrid material's interface is blurred, and its microsize is on the nanometer scale or even down to the level of a molecular compound in some cases . Nowadays, research on hybrid materials is almost in the field of materials, but there have been limited reports on the use of hybrid materials in coagulants …”
Section: Introductionmentioning
confidence: 99%
“…In polymer bridging mechanisms, the adsorption of the particles takes place in a long chain of linear and high molecular weight polymers, leaving dangling heavy coagulant polymer segments to bridge all the particles of the pollutants together, as presented in Figure 2b (Diddens and Heuer (2019). Sweep coagulation is another mechanism that occurs in the presence of chemical coagulants (i.e., metal salts), which are usually added to the water at higher dosages than the solubility of the amorphous hydroxides, and the colloid particles eventually become entrapped within the precipitate and are removed from the suspension (Nan et al, 2016). High electrolyte concentrations in colloidal solutions cause double-layer compression.…”
Section: Coagulation Mechanismsmentioning
confidence: 99%